Distribution of fat, non-osseous lean and bone mineral mass in international Rugby Union and rugby sevens players - Higham, D. G.; Pyne, D. B; Anson, J. M.; Dziedzic, C. E.; Slater, G. J. (International Journal of Sports Medicine, 2014)
Differences in the body composition of international Rugby Union and Rugby Sevens players, and between players of different positions are poorly understood. The purpose of this study was to examine differences in the quantity and regional distribution of fat, non-osseous lean and bone mineral mass between playing units in Rugby Union and Rugby Sevens. Male Rugby Union (n=21 forwards, 17 backs) and Rugby Sevens (n=11 forwards, 16 backs) players from the Australian national squads were measured using dual-energy X-ray absorptiometry. The digital image of each player was partitioned into anatomical regions including the arms, legs, trunk, and android and gynoid regions. Compared with backs, forwards in each squad were heavier and exhibited higher absolute regional fat (Union 43-67%; ±~17%, range of % differences; ±~95% confidence limits (CL); Sevens 20-26%; ±~29%), non-osseous lean (Union 14-22%; ±~5.8%; Sevens 6.9-8.4%; ±~6.6%) and bone mineral (Union 12-26%; ±~7.2%; Sevens 5.0-11%; ±~7.2%) mass. When tissue mass was expressed relative to regional mass, differences between Rugby Sevens forwards and backs were mostly unclear. Rugby Union forwards had higher relative fat mass (1.7-4.7%; ±~1.9%, range of differences; ±~95% CL) and lower relative non-osseous lean mass (-4.2 to -1.8%; ±~1.8%) than backs in all body regions. Competing in Rugby Union or Rugby Sevens characterized the distribution of fat and non-osseous lean mass to a greater extent than a player`s positional group, whereas the distribution of bone mineral mass was associated more with a player`s position. Differences in the quantity and distribution of tissues appear to be related to positional roles and specific demands of competition in Rugby Union and Rugby Sevens.